Coronary artery disease is associated with increased lipoprotein(a) concentrations independent of the size of circulating apolipoprotein(a) isoforms. - Farrer, M; Game, F; Albers, C; Neil, H; Winocour, P; Laker, M; Adams, P; Alberti, K (1994)
Lipoprotein(a) [Lp(a)] concentration and apolipoprotein(a) [apo(a)] isoforms (identified by sodium dodecyl sulfate-polyacrylamide gel electrophoresis [SDS-PAGE] and Western blotting) were determined in a group of 508 asymptomatic Caucasian members of the community and in 318 Caucasian patients with angiographically defined coronary artery disease (CAD). Conventional risk factors for CAD were also measured. Lp(a) concentration was almost twice as high in subjects with CAD (geometric mean, 152 mg/L [geometric SD, 10 to 1398 mg/L]) as in asymptomatic control subjects (geometric mean, 84 mg/L [geometric SD, 21 to 334 mg/L]). Asymptomatic women had higher concentrations of Lp(a) than asymptomatic men. Patients with CAD were older and were more likely to have smoked and to have a first-degree relative with premature CAD (< 55 years of age), and a higher proportion were male. Patients with CAD had higher concentrations of Lp(a) independently of the number of isoform bands expressed. When apo(a) isoforms were allocated to 1 of 10 classes on the basis of their molecular size (Rf versus apoB in SDS-PAGE), patients with CAD did not express an excess of low-molecular-mass (higher concentration) isoforms but did express a higher proportion of double-band phenotypes with fewer "null" phenotypes. The relationship between the two isoform bands in a double-band phenotype was the same in both populations. Isoform mobility was defined as a continuous variable equal to the mobility of a single isoform band (single-band phenotypes) or the mean of the two isoforms in a double-band phenotype. Two variables, isoform mobility and the number of isoform bands expressed, were used to summarize the large range of isoform patterns (at least 45) that could be identified. Isoform mobility, the number of isoform bands expressed, and the presence of CAD were the three most important independent predictors of Lp(a) concentration (descending order). Only sex and LDL cholesterol were additional independent predictors of Lp(a) concentration in step-wise regression models including a wide range of demographic factors and lipid and glycemic risk factors. We conclude that Lp(a) concentration is associated with CAD independently of the isoform pattern expressed. The apo(a) gene locus exerts a strong control over circulating Lp(a) concentration, and a better understanding of the control of expression of the apo(a) gene will be essential to understand the relationship between Lp(a) and CAD.